Evolving business models : how CEO's transform traditional companies - Franz, Christoph; Bieger, Thomas; Herrmann, Andreas, 1964- (Springer, 2017)
This book addresses the core challenges currently faced by traditional companies. In the age of digitization many industries are now challenged by disruptions of the traditional value chain: new competitors are coming into play, traditional products don't sell any more, and profits are at risk. As such, CEOs need to adopt new business models for these established industries, while many companies have to reinvent themselves by developing new products for new markets. In this book, leading CEOs share their experiences in transforming established companies. They provide insights on transforming industries and demonstrate what it takes to redefine companies from the ground up. Issues such as organizational transformation, new product development, implementing a new organizational spirit, and many more are discussed.
Keywords: Business planning.; Chief executive officers.; Management.; elektronické knihy; electronic books